Young pupils' perceptions of their foreign language learning lessons: the innovative use of drawings as a research tool. Issue 2 (15th March 2019) - Millonig, Diana Jean; Stickler, Ursula; Coleman, James A.
ABSTRACT: Classroom research involving young participants' perceptions is difficult and therefore not frequently undertaken. This article describes how an innovative use of drawings supported by pupil clarification of content can diminish difficulties and, more importantly, provide valid and in-depth reliable qualitative data for analysis. The study investigated primary school pupils' perceptions of their foreign language (FL) lessons (English) involving the teaching taking place in the classroom, i.e. approach, methods, strategies and tools used, and pupils' perceptions of English per se . The data of 48 drawings were collected at two primary schools in Austria and analysed through the lens of general and FL learning theories. Finally, a critical comparison with Austrian education policies was made. The findings showed that teachers' classroom practice and their FL ability (pronunciation, grammar) are reflected clearly in the children's drawings and in their attitudes to and enjoyment of the English lessons.